Potential Nutritive Value and Condensed Tannin Contents of Acorns from Different Oak Species - KAYA, E.; KAMALAK, A. (Kafkas Universitesi Veteriner Fakultesi Dergisi, 2012)
The potential nutritive values of acorns of Quercus suber, Quercus branti, Quercus coccifera, Quercus cerris and Quercus infectoria were estimated by chemical composition and in vitro gas production technique. Acorns collected at least 10 different trees in three experimental plots. There were significant (P<0.001) differences in the chemical composition among acorns obtained from different oak species. Crude protein (CP) contents of acorns ranged from 25.48 to 61.94 g/kg dry matter (DM). Neutral detergent fiber (NDF) contents ranged from 231.4 to 326.3 g/kg DM. Acid detergent fiber (ADF) contents ranged from 155.9 to 215.4 g/kg DM. Condensed tannin (CT) contents ranged from 7.2 to 26.7 g/kg DM. Starch contents ranged from 600.0 to 681.5 g/kg DM. Polyethylene glycol (PEG) addition significantly (P<0.001) increased the gas production and some estimated parameters of oak acorns. Although there is no significant (P>0.5) differences in the potential gas production of acorn among oak species when incubated in the absence of PEG, there is significant (P<0.001) differences in the potential gas production of acorn among oak species when incubated in the presence of PEG. Although the estimated organic matter (OMD) and metabolisable (ME) contents of acorn for Q. suber and Q. infectoria were significantly (P<0.001) higher than those for Q. branti, Q. coccifera and Q. cerris when incubated in the absence of PEG, the estimated OMD and ME contents of acorn for Quercus cerris and Q. infectoria were significantly lower than those for Q. suber, Q. branti and Q. coccifera when incubated in the presence of PEG. The improvement in gas production, OMD and ME in the presence of PEG emphasizes the negative effect of tannins on digestibility. As a conclusion, oak acorns have potential nutritive values for ruminant animals such as sheep and goat since acorns have high starch, OMD and ME but low level of CT contents. However these results obtained in the current study should be supported by in vivo feeding experiments.
Keywords: Condensed tannin; digestibility; In vitro gas production; Metabolizable energy; oak acorn; Polyethylene glycol

Effects of herbage ingestion upon ileal digestibility of amino acids in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R.; Nieto, R.; Aguilera, J. F. (JOURNAL OF ANIMAL PHYSIOLOGY AND ANIMAL NUTRITION, 2010)
P>We conducted two experiments with heavy Iberian pigs to determine the ileal digestibility of amino acids (AA) in acorns and freshly cut herbage, and the effects of adding fresh herbage upon the supply of ileal digestible AA when pigs were fed on holm-oak acorns. In Experiment 1, carried out in cannulated pigs of 107 kg bodyweight (BW), daily intake of acorns reached 44.9 g DM/kg0.75 BW. Arg, His and Thr showed the lowest apparent ileal digestibility (AID) values, whereas Met, the branched-chain AA and Phe had the highest coefficients. The AID of total EAA was 0.716 but only 0.222 for NEAA. Most of the digestive and absorptive processes of acorn protein occurred before the hindgut. Acorn provides (per kg DM) 2.27 g apparent ileal digestible Lys and 22.7 g apparent total digestible AA. Standardized ileal digestibility (SID) values for EAA, NEAA and total AA were 0.924 +/- 0.020, 0.784 +/- 0.041 and 0.860 +/- 0.029. In Experiment 2 fresh herbage was given to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg0.75 BW) or as a supplement to acorns (28.4 g DM/kg0.75 BW). When only freshly cut forage was offered the AID of the EAA, NEAA and total AA was close to 0.65 and supplied (per kg DM ingested) 5.61 g AID Lys and 91.7 g digestible AA. Standardized ileal values were 0.744 +/- 0.023, 0.912 +/- 0.038 and 0.831 +/- 0.030 respectively. The addition of fresh forage to the acorns led to a significant decrease in AID of AA in acorn due to digesta transfer to the hindgut: His (p < 0.01), Met (p < 0.001), Phe (p = 0.092), Thr (p < 0.05) and Val (p < 0.05), but Arg, Lys and the branched-chain AA remained unaffected. The main contribution of herbage to AA nutrition of the grazing Iberian pig relies mainly on increasing the supply of digestible AA for pig tissues.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: acorns; amino acids; digestibility; herbage; iberian pig

Cork oak (Quercus suber L.) acorn as a substitute for barley in the diet of rabbits; Effect on In vivo digestibility, growth and carcass characteristics. J. anim - Boubaker, A. Gasmi; Abduli, H.; Lozada, M. R. M. (Journal of Animal and Veterinary Advances, 2007)
In this study 2 experiments were conducted to evaluate the feeding value of cork oak acorn as an energy source for rabbits. Experiment 1 was a digestibility trial using 20 adult rabbits (10 rabbits/group) and experiment 2 was a growth performance and carcass evaluation using 24 growing rabbits in a completely randomised design. Two diets were formulated to contain either 250 g Dry Matter (DM) barley (Barley diet) or 250 g DM oak Acorn (Acorn diet)/kg and included mainly, wheat bran, soybean meal, hay, molasses, calcium phosphate, Cu SO4 and salt. Inclusion of acorn in the diet did not result in any change in odour and fungal contamination nor in the feed intake (p>0.05). However, acorn in the diet decreased the in vivo digestibility by 10.8, 11.5 and 17.5%, respectively, for DM, Organic Matter (OM) and Crude Protein (CP). Although the rabbits fed acorn diet retained less nitrogen than those fed barley diet, they were positive in the nitrogen balance. The final live weight and daily weight gain from weaning through slaughter did not show any significant difference between rabbits fed the control diet and those fed the experimental diet. Similar carcass yield and feed conversion ratio were observed for the 2 groups. Weight of full gastrointestinal, liver, kidney and caecum were not affected (p>0.05) by the presence of acorn in the experimental diet. A more careful evaluation of the real content and digestibility of nutrients from acorn is necessary to evaluate their nutritional value before considering them as a potential feed for rabbits.
Keywords: acorn; digestibility; Growth; rabbit; tannin

Cork oak (Quercus suber L.) acorn as a substitute for barley in the diet of rabbits; Effect on In vivo digestibility, growth and carcass characteristics. J. anim - Boubaker, A Gasmi; Abduli, H; Lozada, M R M (Journal of Animal and Veterinary Advances, 2007)
In this study 2 experiments were conducted to evaluate the feeding value of cork oak acorn as an energy source for rabbits. Experiment 1 was a digestibility trial using 20 adult rabbits (10 rabbits/group) and experiment 2 was a growth performance and carcass evaluation using 24 growing rabbits in a completely randomised design. Two diets were formulated to contain either 250 g Dry Matter (DM) barley (Barley diet) or 250 g DM oak Acorn (Acorn diet)/kg and included mainly, wheat bran, soybean meal, hay, molasses, calcium phosphate, Cu SO4 and salt. Inclusion of acorn in the diet did not result in any change in odour and fungal contamination nor in the feed intake (p>0.05). However, acorn in the diet decreased the in vivo digestibility by 10.8, 11.5 and 17.5%, respectively, for DM, Organic Matter (OM) and Crude Protein (CP). Although the rabbits fed acorn diet retained less nitrogen than those fed barley diet, they were positive in the nitrogen balance. The final live weight and daily weight gain from weaning through slaughter did not show any significant difference between rabbits fed the control diet and those fed the experimental diet. Similar carcass yield and feed conversion ratio were observed for the 2 groups. Weight of full gastrointestinal, liver, kidney and caecum were not affected (p>0.05) by the presence of acorn in the experimental diet. A more careful evaluation of the real content and digestibility of nutrients from acorn is necessary to evaluate their nutritional value before considering them as a potential feed for rabbits.
Keywords: acorn; digestibility; Growth; rabbit; tannin

Effects of herbage ingestion on the digestion site and nitrogen balance in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R; Nieto, R; Lachica, M; Aguilera, J F (LIVESTOCK SCIENCE, 2007)
We conducted two experiments in heavy-weight Iberian pigs to determine: a) the effect of lysine or protein addition - the former as L-lysine-HCl, the latter by fresh cut herbage supplementation - on protein deposition when they were fed on holm-oak acorns; b) the digestibility of energy and nutrients in acorns and freshly cut, mixed herbage; and c) a possible change in the partition of digestion along the gastro-intestinal tract of the pigs fed on acorns with the inclusion of herbage. In Experiment 1, carried out in eight cannulated pigs, the daily intake of acorns reached 44.9 g DM/kg(0.75) BW and the addition of 0.58 g L-lysine/kg of whole acorns failed to alter N retention significantly (P > 0.05). We obtained high coefficients for the apparent total-tract digestibility of dry matter (ApDM(tt), 0.84) and organic matter (ApOM(tt), 0.86) and of gross energy (ApGE(tt), 0.84) in whole acorns. The corresponding ileal values were 0.71, 0.74 and 0.74. The N balance was on average - 1.08 g/day. In Experiment 2, fresh herbage containing principally legumes was offered to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg(0.75) BW) or as a supplement to acorns (28.4 g DM/kg(0.75) BW; in this case the herbage accounted for 22% of the daily DM intake). The apparent ileal digestibilities of OM and GE for herbage accounted for 70 to 77% of the values observed at total-tract level (0.65 and 0.64 respectively). N retention reached 4.21 g/day. Average ApDM(tt), ApOM(tt) and ApGE(tt) in the herbage/whole-acorn mixture were slightly above 0.74. The intake of freshly cut herbage as complementary feed to acorns resulted in a significant transference of digesta from the small intestine to the hind gut together with a substantial decrease in ileal digestibility of nutrients and energy (P < 0.001) and a moderate decline in digestibility at throughout the whole tract (P < 0.01-P < 0.001). On the other hand, the apparent digestibility of total N increased (P < 0.001) and 31% of the N apparently digested was retained in the body of the pigs. We also observed a substantial decrease in the precaecal digestion of the DM (P < 0.01), OM (P < 0.01) and GE (P < 0.05) in acorn kernels. We concluded that the main contribution of herbage to the overall nutrient supply to the grazing Iberian pig would rely upon the provision of amino acid N and also of available minerals, both present in low quantities in acorns. (C) 2007 Elsevier B.V All rights reserved.
Keywords: acorns; digestibility; energy value; herbage; iberian pig

Effects of herbage ingestion on the digestion site and nitrogen balance in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R.; Nieto, R.; Lachica, M.; Aguilera, J. F. (LIVESTOCK SCIENCE, 2007)
We conducted two experiments in heavy-weight Iberian pigs to determine: a) the effect of lysine or protein addition - the former as L-lysine-HCl, the latter by fresh cut herbage supplementation - on protein deposition when they were fed on holm-oak acorns; b) the digestibility of energy and nutrients in acorns and freshly cut, mixed herbage; and c) a possible change in the partition of digestion along the gastro-intestinal tract of the pigs fed on acorns with the inclusion of herbage. In Experiment 1, carried out in eight cannulated pigs, the daily intake of acorns reached 44.9 g DM/kg(0.75) BW and the addition of 0.58 g L-lysine/kg of whole acorns failed to alter N retention significantly (P > 0.05). We obtained high coefficients for the apparent total-tract digestibility of dry matter (ApDM(tt), 0.84) and organic matter (ApOM(tt), 0.86) and of gross energy (ApGE(tt), 0.84) in whole acorns. The corresponding ileal values were 0.71, 0.74 and 0.74. The N balance was on average - 1.08 g/day. In Experiment 2, fresh herbage containing principally legumes was offered to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg(0.75) BW) or as a supplement to acorns (28.4 g DM/kg(0.75) BW; in this case the herbage accounted for 22% of the daily DM intake). The apparent ileal digestibilities of OM and GE for herbage accounted for 70 to 77% of the values observed at total-tract level (0.65 and 0.64 respectively). N retention reached 4.21 g/day. Average ApDM(tt), ApOM(tt) and ApGE(tt) in the herbage/whole-acorn mixture were slightly above 0.74. The intake of freshly cut herbage as complementary feed to acorns resulted in a significant transference of digesta from the small intestine to the hind gut together with a substantial decrease in ileal digestibility of nutrients and energy (P < 0.001) and a moderate decline in digestibility at throughout the whole tract (P < 0.01-P < 0.001). On the other hand, the apparent digestibility of total N increased (P < 0.001) and 31% of the N apparently digested was retained in the body of the pigs. We also observed a substantial decrease in the precaecal digestion of the DM (P < 0.01), OM (P < 0.01) and GE (P < 0.05) in acorn kernels. We concluded that the main contribution of herbage to the overall nutrient supply to the grazing Iberian pig would rely upon the provision of amino acid N and also of available minerals, both present in low quantities in acorns. (C) 2007 Elsevier B.V All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: acorns; digestibility; energy value; herbage; iberian pig

Effect of replacing barley grain with cork oak acorn (Quercus Suber L.) on digestibility, nitrogen balance and growth of goat kids. - Aziza, G. B.; Hedi, A.; Hajer, K.; Rabia, M. (JOURNAL OF ANIMAL SCIENCE, 2006)
The objective of this study was to evaluate the effect of the replacement of barley grain with cork oak acorn (Quercus suber L.) on performance, nutrients intakes, apparent digestibility coefficient and nitrogen balance with growing goats. Ten Boer kids (26.5±2 kg) were individually housed in metabolism cages and were randomly divided into a control (n = 5) and an experimental (n = 5) group. Kids in both groups received (on the basis of crude matter) 500 g/day per head of chopped oat hay and 600 g of concentrate containing barley grain (control group) or oak acorn (experimental group). Digestibility coefficients of dietary components were reduced as a result of acorn substitution for barley. Nitrogen retention (g/day) was positive for experimental group (6.18) but lower than for control group (8.72). The average consumption of digestible components, expressed in g kg-1 LW 0.75 for the control and experimental groups was, respectively, 51.5 and 41.5 (OM) and 7.9 and 6.0 (CP), resulting in weight gains of 80 and 43 g/day.
The following values have no corresponding Zotero field: pub-location: 1111 NORTH DUNLAP AVE, SAVOY, IL 61874 USA publisher: AMER SOC ANIMAL SCIENCE
Keywords: digestibility; kids; oak acorn

Effect of replacing barley grain with cork oak acorn (Quercus Suber L.) on digestibility, nitrogen balance and growth of goat kids. - Aziza, G B; Hedi, A; Hajer, K; Rabia, M (JOURNAL OF ANIMAL SCIENCE, 2006)
The objective of this study was to evaluate the effect of the replacement of barley grain with cork oak acorn (Quercus suber L.) on performance, nutrients intakes, apparent digestibility coefficient and nitrogen balance with growing goats. Ten Boer kids (26.5±2 kg) were individually housed in metabolism cages and were randomly divided into a control (n = 5) and an experimental (n = 5) group. Kids in both groups received (on the basis of crude matter) 500 g/day per head of chopped oat hay and 600 g of concentrate containing barley grain (control group) or oak acorn (experimental group). Digestibility coefficients of dietary components were reduced as a result of acorn substitution for barley. Nitrogen retention (g/day) was positive for experimental group (6.18) but lower than for control group (8.72). The average consumption of digestible components, expressed in g kg-1 LW 0.75 for the control and experimental groups was, respectively, 51.5 and 41.5 (OM) and 7.9 and 6.0 (CP), resulting in weight gains of 80 and 43 g/day.
Keywords: digestibility; kids; oak acorn

Composition and metabolizable energy of feed used by fallow deer (Dama dama) in a coastal Mediterranean ecosystem - Poli, B M; Focardi, S; Tinelli, A (Small Ruminant Research, 1996)
Data on the impact of a population of about 1000 (spring estimate) fallow deer (Dama &ma) on eight shrubs and mono- and dicotyledonous plants were collecred in a coastal Mediterranean environment from December 1990 to March 1992. Four species of shrubs (Cistus salvifoiius, Phillyrea larifolia, Rubus ulmifolius. Quercus ibex) and mixed graminoids were preferentially consumed. In autumn-winter the acorns of several species, Q. cerris and Q. ilex in particular, were also consumed. We determined the chemical composition, in vivo digestibility coefficients and metabolizable energy content of the feed. On average, R. ulmifolius had the lowest fibre content (18% DM) and the highest protein content (12% DM), organic matter digestibility (59%) and metabolizable energy value (2083 kcal ME kg- ’ DM). C. saluifolius, P. fafifolia and mixed graminoids did not differ significantly in organic matter digestibility (OMD) and nutritive value (I 801, 1765 and 1557 kcal ME kg-’ DM, respectively), while Q. ilex had the lowest nutrient estimates with 32% OMD and 1362 kcal ME kg-’ DM. Forage quality traits usually peaked in spring and autumn. Metabolizable energy was positively correlated with protein, neutral detergent fibre and N-free extractives contents, and negatively correlated with the acid detergent fibre content. Acorns were generally highly digestible; in particular, the seed of Q. farniu and Q. ilex showed 80% and 83% OMD, respectively. In a Mediterranean environment the summer seems the most critical season for fallow deer. The results of this work are important for assessing the carrying capacity of wild Mediterranean ecosystems for fallow deer.
Keywords: digestibility; Fallow deer; Feed quality; in vitro; Mediterranean ecosystems

Effects of oak ( Quercus ilex) tannins on digestion and nitrogen balance in sheep and goats - Narjisse, H; Elhonsali, M A; Olsen, J D (Small Ruminant Research, 1995)
Sheep and goats exhibited different levels of tolerance to the effects of tannins extracted from oak leaves (Quercus ilex) Feed intake, N balance, and rumen ammonia concentrations decreased by 8%, 159% and 50%, respectively, in sheep infused intraruminally with tannins (P <0.05). Similar measurements were not depressed (P> 0.05) in goats although mean rumen ammonia content was 39% less. In vivo DM digestibility was not significantly different for either sheep or goats. Averaged in vitro fermentation capacity was depressed 10% by tannin (8-12% concentration) in the rumen fluid from non-infused sheep given the same diet, but was improved by 9% for goats. Finally, tannin-infused goats lost in urine only 17% of the N ingested, while tannin-infused sheep excreted as much as 44%. The superiority of goats in dealing with tannin might result from the greater ability of their microbial population to degrade tannins, and/or their higher urea recycling and salivary secretion capabilities. Results derived from this study indicate that goats may be more suitable for grazing in oak woodland, especially during the season when alternative forage availability is scarce.
Keywords: digestibility; Feed intake; Goats; Quercus; Sheep; tannin

THE NUTRITIONAL CARRYING-CAPACITY OF 4 MEDITERRANEAN HABITATS FOR FALLOW DEER (DAMA-DAMA) - Focardi, S; Poli, B M; Tinelli, A (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1995)
The assessment of the trophic value of the most consumed feed by fallow deer in a coastal mediterranean landscape (Rubus ulmifolius, Cistus salvifolius, Phyllirea latifolia, Quercus ilex and graminoids) was based on in vitro digestibility trials, performed throughout the year (1 set of samples per season) using rumen inocula from wild fallow deer from the Preserve of Castelporziano, collected simultaneously with the vegetal samples. Moreover, in vivo digestibility coefficients have been estimated by using standard feed (for fallow deer) of known in vivo digestibility. Using the digestibility coefficients, the metabolizable energy yield of studied forage items was computed. Information about plant biomass, structure of fallow deer population, metabolizable energy yields, estimates of forage intake and energy requirements were combined using the model presented by Hobbs and Swift (1985) to evaluate the nutritional carrying capacity of four typical mediterranean habitats (natural evergreen oak wood, scrub mixed plantations of Quercus ilex and Pinus pinea, open pastures). Spring represents the most favourable situation, while summer, autumn and winter exhibit similar values of carrying capacity of about 15-20 deer/100 ha. Mixed plantations of Pinus pinea and Q. ilex seem to be the most productive condition for fallow deer.
APS
Keywords: Cistus salvifolius; digestibility; fallow dear; mediterranean landscape; Phyllirea latifolia; Quercus ilex; Rubus ulmifolius; trophic value